FISCAL DECENTRALIZATION AND REGIONAL DISPARITIES IN INDONESIA: A DYNAMIC PANEL DATA EVIDENCE - Suwanan, Ahmad Fawaiq; Sulistiani, Eka Heni (Journal of Indonesian Economy and Business, 2009)
The public sector decentralization advantages and disadvantages are widely discussed in economics and political science. While some economists argue that decentralization leads to an optimal provision of public services and a promotion of economic growth, others emphasize the dangers of competition associated with decentralization between subnational governments especially for interregional redistributive reasons. This researchstudies empirically the impact of fiscal decentralization on regional disparities using dynamic panel data for 33 provinces in Indonesia from 2001 to 2008. Fiscal decentralizationis represented by revenue decentralization (revdec) and regional disparity by gini coefficient. The major result of this study is that a high degree of decentralization is connected with low regional disparities. Hence, poor regions have no disadvantages from decentralization, quite the contrary.Keywords: decentralization, regional disparity, inequality, dynamic panel data evidence